2016
DOI: 10.1080/21505594.2016.1237332
|View full text |Cite
|
Sign up to set email alerts
|

The vaginal mycobiome: A contemporary perspective on fungi in women's health and diseases

Abstract: Most of what is known about fungi in the human vagina has come from culture-based studies and phenotypic characterization of single organisms. Though valuable, these approaches have masked the complexity of fungal communities within the vagina. The vaginal mycobiome has become an emerging field of study as genomics tools are increasingly employed and we begin to appreciate the role these fungal communities play in human health and disease. Though vastly outnumbered by its bacterial counterparts, fungi are impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 132 publications
(120 reference statements)
6
121
1
1
Order By: Relevance
“…Mycobiome studies have been performed for most mucosal surfaces including the oral cavity [6], GI tract [7,8], vagina [9,10], lung [11,12], and skin [13,14]. Over 75 genera of fungi have been identified in the oral cavity alone, which can seed the respiratory or GI tract mycobiome.…”
Section: Niche-specific Fungal Symbiontsmentioning
confidence: 99%
“…Mycobiome studies have been performed for most mucosal surfaces including the oral cavity [6], GI tract [7,8], vagina [9,10], lung [11,12], and skin [13,14]. Over 75 genera of fungi have been identified in the oral cavity alone, which can seed the respiratory or GI tract mycobiome.…”
Section: Niche-specific Fungal Symbiontsmentioning
confidence: 99%
“…Despite a wide body of knowledge about the composition of vaginal microbiota exists, little is known about the composition of the vaginal mycobiome. Recent studies (Guo et al, 2012;Bradford and Ravel, 2017) have reported that in healthy women, Ascomycota is the predominant phylum, followed by Basidiomycota and Oomycota. Candida, Saccharomyces, Aspergillus, Cladosporium, and Alternaria represent the commonly genera of the vaginal mycobiome (Guo et al, 2012;Drell et al, 2013).…”
Section: Vaginal Microbiotamentioning
confidence: 99%
“…The vaginal microbiota is largely dominated by bacteria (Lactobacillus spp.) but comprises fungi and viruses also, [116][117][118] with all three playing important roles in reproductive health. [117][118][119] The composition of the vaginal microbiota is heavily dependent on age, stage of menstrual cycle, hormonal fluctuations, sexual behaviour, and also the use of probiotics and antibiotics.…”
Section: Reproductive Tractmentioning
confidence: 99%